The Low-Temperature Weathering of the Grønnedal-Íka Carbonatite-Alkaline Silicate Igneous Complex in Southwest Greenland - Sigríður María Aðalsteinsdóttir 1993- (2021)
The Grønnedal-Íka igneous complex in SW-Greenland is composed of layered nepheline-syenite suites and a carbonatite plug. It is believed that weathering of the complex generates alkaline pH water, leading to the precipitation of the submarine ikaite tufa pillars in Ikka Fjord. Ikaite is a hydrated calcium carbonate mineral only stable at low water temperature (<~6°C). The complex is one of many interesting features within geosciences, both for its distinct geology and biota. The petrology and major chemical constraints of the complex are relatively well studied; however, few studies have been focused on chemical weathering processes. This study attempts to join petrology and water geochemistry to get insight into the water composition formed via water-rock interactions during low-temperature weathering. The nepheline syenites of the complex are generally on the boundary being alkali saturated and alkali undersaturated, while the carbonatites are rich in carbonates and CO2. The primary minerals of the nepheline-syenites are orthoclase (28%), albite (24%), nepheline (25%), aegirine-augite (6%), riebeckite (2%), ferro-richerite (2%), biotite, and apatite (1%). Two different carbonatites were studied, 1) calciocarbonatite dominantly composed of calcite (99%) and 1% fluorite minerals, and 2) ferruginous calciocarbonatite, with an unusual mineral assemblage of calcite (64%), ankerite (10%), riebeckite (8%), REE minerals and fluorites (1%). New insight into the rare earth element (REE) phases and fluorite minerals within the carbonatites suggests that the complex might be richer in fluorites and REE minerals than previously thought. Geochemical calculations, simulating the process of the rock weathering, indicate formation of water characterized by high pH >10, elevated Na and low CO2 concentrations, that result in the formation of (Fe, Al, Mn) oxides, (Fe-Na, Fe-K, Fe-Fe, Na, K) smectite-group and (K-Mg) illite clays, and (Ca) carbonates. According to modelling, these alkaline fluids can lead to the ...